2017
DOI: 10.5758/vsi.2017.33.3.108
|View full text |Cite
|
Sign up to set email alerts
|

Usefulness of Percutaneous Puncture in Insertion of Totally Implantable Venous Access Devices in Pediatric Patients

Abstract: PurposeTotally implantable venous access devices (TIVADs) are commonly used in pediatrics for the administration of chemotherapy, antibiotics, or parenteral nutrition. TIVADs can be implanted using various techniques, including surgical cutdown (SC) and percutaneous puncture (PP). Recently, percutaneous TIVAD became popular in adults, but studies comparing between PP and SC group in pediatric patients are rare.Materials and MethodsData were collected and analyzed retrospectively from 23 patients who underwent … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 6 publications
(13 reference statements)
0
3
0
Order By: Relevance
“…One study reported USG percutaneous puncture of totally implantable venous devices had similar success rates, procedure times, and complication rates when compared to surgical cutdown methods. 48 Another study found that insertion of totally implantable venous devices by using ultrasound guidance was significantly more effective in reducing complication rates, had shorter procedure times, and was more cost-efficient compared to open surgical cutdown techniques. 71 However, recommendations for other visualization techniques in pediatric populations, including NIR light (vessel visualization) and ECG (catheter-tip confirmation) device use, were scant.…”
Section: Vessel Visualizationmentioning
confidence: 99%
“…One study reported USG percutaneous puncture of totally implantable venous devices had similar success rates, procedure times, and complication rates when compared to surgical cutdown methods. 48 Another study found that insertion of totally implantable venous devices by using ultrasound guidance was significantly more effective in reducing complication rates, had shorter procedure times, and was more cost-efficient compared to open surgical cutdown techniques. 71 However, recommendations for other visualization techniques in pediatric populations, including NIR light (vessel visualization) and ECG (catheter-tip confirmation) device use, were scant.…”
Section: Vessel Visualizationmentioning
confidence: 99%
“…We have read with keen interest the article titled, “Usefulness of percutaneous puncture in insertion of totally implantable venous access devices in pediatric patients” by Choi et al [ 1 ] published in the September 2017 issue of Vascular Specialist International. We congratulate the authors for extensive research and we would like to share our experience with Port-A-Caths (PACs) in children with hematologic/ oncologic diseases.…”
mentioning
confidence: 99%
“…PACs are commonly used in children who require long-term central venous access for medications or nutrition [ 1 ]. Although these devices are extremely necessary, they pose a serious risk of complications including infection, thrombosis, and mechanical occlusions [ 2 4 ].…”
mentioning
confidence: 99%